2018
DOI: 10.1016/j.schres.2017.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Childhood unusual experiences in community Child and Adolescent Mental Health Services in South East London: Prevalence and impact

Abstract: Assessing UEDs routinely in CAMHS is feasible, and suggests that around two thirds of assessed referrals could potentially benefit from interventions targeting UEDs. Additional training may be required for the CAMHS workforce to address this need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…As outlined by Gin et al . (), young people may not disclose these experiences unless they are directly asked about them. Although the development of youth mental health services is still in its relative infancy, the results of this study have equal relevance for both traditional Child and Adolescent and Adult Mental Health service settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As outlined by Gin et al . (), young people may not disclose these experiences unless they are directly asked about them. Although the development of youth mental health services is still in its relative infancy, the results of this study have equal relevance for both traditional Child and Adolescent and Adult Mental Health service settings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these studies, Gin et al . () recently screened for PLEs in young people accessing traditional Child and Adolescent Mental Health Services (CAMHS) for under 18s and showed that around two‐thirds of young people may benefit from targeted interventions for PLEs. The prevalence of PLEs in older adolescents and young adults accessing mental health services is, however, largely unknown, as is the practicality of routine screening within this client group.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, direct evaluation through self report of psychotic-like symptoms experienced by children and adolescents attending community mental health clinics was found to reach 68%, with 60% of these being associated with distress or impairment. 25 Finally, the multiple routes into psychosis, affected both by genetic liability 26 and psychosocial adversity and abuse 27 may not always provide a good pointer towards EOP as they are not unique to psychosis, also being associated with a wide range of brain changes and mental and behavioural disorders with commonly adolescent onset. [28][29][30] The interaction between brain maturational processes, environmental insults and proneness to mental illness are more likely to give mixed or hard-todeconstruct clinical presentations in this age when EOP incidence gradually reaches its peak.…”
Section: Dilemma Number 1: What Are We Treating?mentioning
confidence: 99%
“…For example, Gin et al (2018) found a much higher prevalence of PLEs via their self-report measure than typically found via interview assessment (Horwood et al, 2008;Kelleher et al, 2014;Pontillo et al, 2016). Another limitation of birth cohort studies is that the findings may underestimate the true incidence rates of those who developed SSD.…”
Section: Terminology and Measurement Of Epmentioning
confidence: 96%